Governance of the bioeconomy: A global comparative study of national bioeconomy strategies - Thomas Dietz; Jan Börner; Jan Janosch Förster; Joachim von Braun (University of Bonn, Center for Development Research (ZEF), 2018)
More than forty states worldwide currently pursue explicit political strategies to expand and promote their bioeconomies. This paper assesses these strategies in the context of the global Sustainable Development Goals (SDGs). Our theoretical framework differentiates between four pathways of bioeconomic developments. The extent, to which bioeconomic developments along these pathways lead to increased sustainability, depends on the creation of effective governance mechanisms. We distinguish between enabling governance and constraining governance as the two fundamental political challenges in setting up an effective governance framework for a sustainable bioeconomy. Further, we lay out a taxonomy of political support measures (enabling governance) and regulatory tools (constraining governance) that states can use to confront these two political challenges. Guided by this theoretical framework, we conduct a qualitative content analysis of 41 national bioeconomy strategies to provide systematic answers to the question of how well designed the individual national bioeconomy strategies are to ensure the rise of a sustainable bioeconomy.
Keywords: O3; Q0; L5; H0; 330; Bioeconomy; Governance; Development Policy; Innovation; Technology; Bio-based